A review of mantle xenoliths in volcanic rocks from southern Victoria Land, Antarctica - Adam P. Martin; A.F. Cooper; C.L. Doherty; J.A. Gamble (2021)
A compilation of published mineral and whole rock chemistry of mantle xenoliths of 107 southern Victoria Land